2021
DOI: 10.1123/jsr.2019-0346
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Proprioceptive Training on Directional Dynamic Stabilization

Abstract: Objectives: Significant loss of playing time and the impact of treatment costs due to lower limb injury in football demonstrates a need for improved protocols for injury risk reduction. The aim of the present study is to assess the effect of a proprioceptive training program on the lower limb dynamic stability of elite footballers. Methods: A total of 16 elite premier league footballers were randomly allocated by matched pair design to a 8-week proprioception training group (group A, n = 8) or nontraining grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…12,13,14 Current findings, in agreement with previous studies report positive correlations between hamstring function and directional dynamic stability. 9 Main findings within this body of work indicate significant differences between pre exercise measures and +48hrs for all directions of stability, with no differences observed at 72hr+. Interestingly, no significant differences were observed for A-P stability when compared to pre fatigue measures, despite a 22% average increase in scores.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…12,13,14 Current findings, in agreement with previous studies report positive correlations between hamstring function and directional dynamic stability. 9 Main findings within this body of work indicate significant differences between pre exercise measures and +48hrs for all directions of stability, with no differences observed at 72hr+. Interestingly, no significant differences were observed for A-P stability when compared to pre fatigue measures, despite a 22% average increase in scores.…”
Section: Discussionmentioning
confidence: 67%
“…Resulting in excessive load being exerted through the ACL. 19,20 It is suggested that decreased functional strength of the hamstrings may have an impact on directional dynamic stability performance, 9 and with the addition of acute fatigue exposure or insufficient recovery this risk could be heightened.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations